2009
DOI: 10.1093/molbev/msp301
|View full text |Cite
|
Sign up to set email alerts
|

Demographic histories of four spruce (Picea) species of the Qinghai-Tibetan Plateau and neighboring areas inferred from multiple nuclear loci

Abstract: Nucleotide variation at 12-16 nuclear loci was studied in three spruce species from the Qinghai-Tibetan Plateau (QTP), Picea likiangensis, P. wilsonii, and P. purpurea, and one species from the Tian Shan mountain range, P. schrenkiana. Silent nucleotide diversity was limited in P. schrenkiana and high in the three species from the QTP, with values higher than in boreal spruce species, despite their much more restricted distributions compared with that of the boreal species. In contrast to European boreal speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
150
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(166 citation statements)
references
References 78 publications
14
150
2
Order By: Relevance
“…menziesii (Eckert et al, 2009a;Wei et al, 2011). In a recent study reporting the sequencing of 14-16 genes in 3 Picea species from the Qinghai-Tibetan plateau (Li et al, 2010), mean r 2 values were also higher than those estimated for P. glauca or P. abies (Table 4). The authors suggested that pooling data from different species might have inflated r 2 , given that recombination rates were admittedly high (Li et al, 2010).…”
Section: Ld Patternsmentioning
confidence: 83%
See 2 more Smart Citations
“…menziesii (Eckert et al, 2009a;Wei et al, 2011). In a recent study reporting the sequencing of 14-16 genes in 3 Picea species from the Qinghai-Tibetan plateau (Li et al, 2010), mean r 2 values were also higher than those estimated for P. glauca or P. abies (Table 4). The authors suggested that pooling data from different species might have inflated r 2 , given that recombination rates were admittedly high (Li et al, 2010).…”
Section: Ld Patternsmentioning
confidence: 83%
“…Thus, structure in the data set might not be the only contributing factor to the higher average r 2 value observed in genes from these Asian spruce taxa. Although they might have been less affected by glaciations than boreal spruces (Li et al, 2010), the restricted distribution of some of these species might also be indicative of smaller historical population size, potentially leading to increased LD. Further studies are required, whether of empirical or simulation nature, to investigate the sensitivity of LD estimates to these factors.…”
Section: Ld Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This independent inheritance of two cytoplasmic genomes provides the opportunity for tracing paternal and maternal genetic changes within a single species because of different rates of gene flow and for discriminating female and male parents of hybrids (Ennos, 1994;Liston et al, 2007;Wachowiak and Prus-G"owacki, 2008). In addition, the analysis of multiple nuclear loci can be used to examine interspecific divergence and clarify parental origins of putative hybrid species (for example, Ma et al, 2006;Li et al, 2010). Thus, here we use sequences from cpDNA, mtDNA and eight nuclear genes to address the following specific questions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the second view, high species richness in these regions is a consequence of rapid adaptive radiation due to diverse and complex topography, especially for most of the species-rich genera (e.g., Cupressus spp., Xu et al 2010; Rheum spp., Sun et al 2012; Primula spp., Zhang et al 2013;reviewed in Liu et al 2014), or resulted from limited gene flow caused by repeated bottlenecks in the Quaternary, as exampled by Picea spp. (Li et al 2010), Tsuga dumosa (Cun and Wang 2010), Aconitum gymnandrum (Wang et al 2009). Third, high intra-specific and interspecific diversity can be a result of topographic changes due to river recaptures, e.g., Terminalia franchetii , Salweenia spp.…”
Section: Introductionmentioning
confidence: 99%